2006
DOI: 10.1146/annurev.arplant.57.032905.105215
|View full text |Cite
|
Sign up to set email alerts
|

Responding to Color: The Regulation of Complementary Chromatic Adaptation

Abstract: The acclimation of photosynthetic organisms to changes in light color is ubiquitous and may be best illustrated by the colorful process of complementary chromatic adaptation (CCA). During CCA, cyanobacterial cells change from brick red to bright blue green, depending on their light color environment. The apparent simplicity of this spectacular, photoreversible event belies the complexity of the cellular response to changes in light color. Recent results have shown that the regulation of CCA is also complex and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
213
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(220 citation statements)
references
References 96 publications
5
213
1
1
Order By: Relevance
“…Thus, the regulatory factor that controls the previously reported GL-dependent upregulation of tonB remains to be identified. However, GL upregulation of tonB expression could depend upon recognized pathways such as the GL inductive Cgi pathway that has been established but not fully characterized at the molecular level in F. diplosiphon (Kehoe & Gutu, 2006). This first report of a biochemical function for a cyanobacterial TonB protein establishes FdTonB as a novel GL-regulated effector required for photoregulation of cellular morphology in F. diplosiphon.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, the regulatory factor that controls the previously reported GL-dependent upregulation of tonB remains to be identified. However, GL upregulation of tonB expression could depend upon recognized pathways such as the GL inductive Cgi pathway that has been established but not fully characterized at the molecular level in F. diplosiphon (Kehoe & Gutu, 2006). This first report of a biochemical function for a cyanobacterial TonB protein establishes FdTonB as a novel GL-regulated effector required for photoregulation of cellular morphology in F. diplosiphon.…”
Section: Discussionmentioning
confidence: 90%
“…The changes that occur during CCA have been well characterized in the freshwater cyanobacterium Fremyella diplosiphon, which is also designated Calothrix sp. PCC 7601 (Kehoe & Gutu, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Pseudanabaena benefited from CCA only if fluctuations in underwater light color were slow compared with the time required for CCA, corresponding to slow mixing processes or infrequent storms in their natural habitat . We hypothesize that PC-rich strains in cluster I have lost the capacity of CCA recently by the loss or presence of dysfunctional genes required to synthesize the PE disks in the phycobilisome, or the genes like rcaE which is needed for the control of CCA (Terauchi et al, 2004;Kehoe and Gutu, 2006). Knockout experiments targeting the rcaE gene showed that this gene is needed for responsiveness to both red and green light under CCA (Terauchi et al, 2004).…”
Section: Genetic Diversification Of Pseudanabaena Populationsmentioning
confidence: 99%
“…Some strains display complementary chromatic adaptation (CCA). This process allows these organisms to regulate the ratio of the accessory photosynthetic pigments phycocyanin (PC) and phycoerythrin (PE), which helps them to adapt to the prevailing light spectrum (reviewed by Kehoe and Gutu (2006)) thereby favoring their persistence in competition against other species (Stomp et al, 2004. Most cultured strains reveal gliding motility and some are capable of anaerobic N 2 fixation (Rippka and Herdman, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In marine Synechococcus spp, the genes for the metabolism of phycobiliproteins are concentratedly distributed in several operons or gene clusters. The cyanobacteria can intimately attune to ambient light conditions with shifts in the levels of their phycobilisome composition, i.e., chromatic acclimation (Kehoe and Gutu, 2006), which can be achieved by the regulations of a twocomponent signal system (Gutu and Kehoe, 2012). However, in Prochlorococcus, most of the genes for phycobiliproteins disappear, and only a small set of genes for phycoerythrin Type III and their reductases is conserved in the genome, which suggests that the genes for phycobilierythrin are being lost through selection in the evolutionary process (Ting et al, 2001).…”
Section: Cyanobacterial Genomicsmentioning
confidence: 99%